PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA PADA KEPUASAN KERJA, KOMITMENKARYAWAN DAN NIAT BERPINDAH - Aditya Chandra Maulana; Muhammad Cholil (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2016)
This studyaimed toanalyze the influence ofcareer development to job satisfaction; the effect of salary to job satisfaction; the effect on turn over intentions salary; the effecton employee commitment job stability; the effect of job satisfaction on employee commitment; the effect of job satisfaction on turn over intentions; as well as the influence of employee commitment to turn over intentions. Samples were employees of PT. Bank Negara Indonesia (Persero) Tbk Main Branch Office Surakarta that as many as 105 respondents. The method used for sampling are using non-probability sampling technique that is proportionate random sampling. Mean while analytical methods used are Structural EquationModel (SEM).Results for hypothesis testing indicates that career development significant positive effect on job satisfaction; Salari essignificant positive effect on job satisfaction; Salaries no significant effect on turn over intentions; job stability significant positive effect on employee commitment; job satisfaction significant positive effect on employee commitment; job satisfaction no significant effect on turn over intentions; and employee commitment significant negative effect on turn over intentions.